2021
DOI: 10.1097/ta.0000000000003418
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin titrated by anti-Xa levels reduces venous thromboembolism in trauma patients

Abstract: BACKGROUND:Trauma is a major risk factor for the development of a venous thromboembolism (VTE). After observing higher than expected VTE rates within our center's Trauma Quality Improvement Program data, we instituted a change in our VTE prophylaxis protocol, moving to enoxaparin dosing titrated by anti-Xa levels. We hypothesized that this intervention would lower our symptomatic VTE rates. METHODS:Adult trauma patients at a single institution meeting National Trauma Data Standard criteria from April 2015 to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…At the other end of the spectrum, patients in our study with subprophylactic anti-Xa levels were more likely to develop PE ( p < 0.001). This echoes prior literature, where active adjustment of anticoagulation to achieve and sustain target prophylactic anti-Xa levels has been demonstrated to significantly reduce VTE incidence, 31 whereas remaining at subprophylactic anti-Xa levels confers significantly elevated risk of VTE and subsequent morbidity and mortality 30 . It should be noted that, of the 12 patients in our study classified as having pulmonary emboli, only 3 were also diagnosed with DVT.…”
Section: Discussionsupporting
confidence: 82%
“…At the other end of the spectrum, patients in our study with subprophylactic anti-Xa levels were more likely to develop PE ( p < 0.001). This echoes prior literature, where active adjustment of anticoagulation to achieve and sustain target prophylactic anti-Xa levels has been demonstrated to significantly reduce VTE incidence, 31 whereas remaining at subprophylactic anti-Xa levels confers significantly elevated risk of VTE and subsequent morbidity and mortality 30 . It should be noted that, of the 12 patients in our study classified as having pulmonary emboli, only 3 were also diagnosed with DVT.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, we identified four observational studies ( n = 5180), that examined the use of intermediate–high enoxaparin dose (40 mg every 12 h) versus conventional dose (30 mg every 12 h) [ 68 71 ]. The pooled estimates showed that intermediate–high enoxaparin dose was associated with reduced VTE (RR 0.64, 95% CI 0.42–0.97; very low quality) and PE (RR 0.32, 95% CI 0.14–0.76; very low quality).…”
Section: Resultsmentioning
confidence: 99%
“…However, the reduction in DVT risk was statistically nonsignificant (RR 0.65, 95% CI 0.37–1.14; very low quality). Three observational studies ( n = 5111) reported on mortality outcome with unclear benefit (RR 1.14, 95% CI 0.93–1.40; very low quality) [ 68 , 69 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common fixed dose comparison was enoxaparin 30 mg SC BID. 13,20,22,30,31,33,[35][36][37]40 The median (Q1-Q3) in-hospital VTE incidence was 4.9% (3.3%-9.2%). There were 6 studies reporting use of screening ultrasound for detection of DVT, 19,22,30,34,38,41 for which the median (Q1-Q3) VTE incidence was 9.1% (4.9%-10.2%).…”
Section: Resultsmentioning
confidence: 99%